Fracture mechanics criterion of time-dependent crack initiation from interface free-edge in adhesively bonded butt joints. (December 2017) - Takahashi, Yoshimasa; Inoue, Kosuke; Takuma, Masanori; Saitoh, Ken-ichi; Sato, Tomohiro
Highlights: Time-dependent crack initiation from interface free-edge is experimentally evaluated. Crack initiation life varied four orders of seconds with nominal stress change. Fracture criterion successfully expressed by creep stress/strain singular parameters. Abstract: The time-dependent crack initiation from the interface free-edge of adhesively bonded axisymmetric columnar butt joints (epoxy/SUS, edge shape: 90°/90°) was investigated in detail. With the change of applied stress level, σn, the butt joints exhibited crack initiation life, t C, that varied about four orders of seconds (10 2 –10 6  s). Such a clear time-dependent life property was then studied in terms of the fracture mechanics. The near-edge stress/strain field at the crack initiation was numerically evaluated with the finite element method (FEM) by applying the time-hardening creep law to the epoxy resin. It was found that the critical asymptotic stress field along the interface represented by the combination of two parameters, λ σ cr (creep stress singularity index) and K σ cr (creep stress intensity factor), satisfies a unique relation irrespective of (σn, t C ) sets. The same tendency was also confirmed when the near-edge total strain field parameters were employed. These results indicate that the K -λ criterion, originally developed for static fracture problems, still holds its validity in the time domain.